Penderitaan Tokoh Minut dalam Cerpen Ibu Tiri Karya Afifah Ardi - Dina Noviani Indria Saputri; Vika Windriyani; Eva Dwi Kurniawan (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2024)
This journal writing is based on the short story stepmother by Afifah Ardi. Explains and provides an in-depth picture of what the character Minut faces, a child who experiences physical violence from his stepmother and bears the burden of being a substitute mother for his younger siblings. The formulation of the problem is how the physical violence and mental pressure experienced by the character Minut can affect his physical and psychological development. The background of this short story is related to the phenomenon of family violence and its long-term impact on children. The research method used is hermeneutics, with a focus on interpretation and analysis of short story texts. The theoretical study includes previous research on violence against female characters in literature and its relevance to the suffering of Minut characters. The results of the discussion show that physical violence and mental pressure have an impact not only physically, but also psychologically, creating an internal struggle for Minut’s character between obligation and personal bitterness. Minut’s character, even though he is full of disappointment, resentment and fatigue, still shows strength of character in protecting his younger siblings. The conclusion highlights the urgency of raising awareness of family violence and the need for action to protect children’s rights.